BUILDING INTERPROFESSIONAL TEAMWORK SKILLS FOR HEALTHCARE ADMINISTRATION AND HEALTH SCIENCES STUDENTS VIA ONLINE EDUCATION. - RUILING GUO; AUSTILL, LORI; GINNETTI, RICHARD M.; LIANG YAN (Journal of Health Administration Education)
The purpose of this study was to explore effective methods of teaching interprofessional teamwork skills to students in healthcare administration and health sciences programs through a fully online learning environment, and to assess the achievement of student learning outcomes related to the utilization of soft skills in teamwork. A cross-sectional study was conducted among 201 undergraduate students in over 14 health professions, with 167 completing the survey, for a response rate of 83%. ANOVA and frequency analyses were performed using SPSS. Ninety-one percent (152/167) of students self-reported gaining teamwork and collaboration skills via an online group project, and 90% (151/167) self-reported that the acquired skills would help their future professions in team-based healthcare systems. Seventy-seven percent (128/167) identified teamwork and collaboration as the top benefit of the group project. Overall, 92% (154/167) reported that group project activities were a positive learning experience. The study results indicated no statistically significant difference in the perceived benefits of the group project among healthcare administration, rehabilitation, and medical/health sciences students (F = 0.697, p = 0.555). This study demonstrated the success and benefits of creating a group work environment within a fully online learning format to teach health profession students interprofessional teamwork skills.